Pengaruh Pendidikan Karakter terhadap Kecerdasan Emosional Remaja Kelas XI di SMA Negeri 1 Malaka Barat Besikama - Anselmus Mones; Cresensius Paulus Boli Toba (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
The purpose of this study was to determine the effect of character education on students emotional intelligence, and also measure how much influence the character's education had on the emotional intelligence of teenagers. Researchers used quantitative research methods to be able to know and at the same time measure the effect between variable X and variable Y. This research was conducted at SMA Negeri 1 Malaka Barat, especially class XI with a total number of students of 160. Determination of the sample was selected using random sampling techniques, while the number the sample was determined by the Slovin formula of 62 students. The determination of this sample is considered representative and can be justified because it uses standard techniques that can be trusted. The research data were collected through observation and questionnaire distribution, and then an analysis was carried out with the previous normality test, product moment correlation test and simple regression equation. The research data shows that between character education in schools and emotional intelligence have a "strong" relationship, where the results of the product moment correlation test found a correlation coefficient of 0.784 or as much as 61.46% if converted using the coefficient of determination test. From these data it can be concluded that there is a strong influence between character education and adolescent emotional intelligence of 61.46% and the remaining 38.54% is determined by other factors.